Bridesmaids - Feig, Paul.; Mumolo, Annie; Wiig, Kristen, 1973-; Rudolph, Maya.; Byrne, Rose.; McCarthy, Melissa, 1969-; McLendon-Covey, Wendi, 1969-; Kemper, Ellie; O'Dowd, Chris, 1980-; Universal Pictures (Firm); Relativity Media; Apatow Productions; et al. (Universal City, CA : Universal Studios Home Entertainment, 2011)
Annie's life is a mess. But when she finds out her lifetime best friend is engaged, she simply must serve as Lillian's maid of honor.
Originally released as a motion picture in 2011.
Director of photography, Robert Yeoman ; editors, William Kerr, Mike Sale ; music, Michael Andrews.
Maya Rudolph, Kristen Wiig, Rose Byrne, Melissa McCarthy, Wendi McLendon-Covey, Ellie Kemper, Chris O'Dowd.
Theatrical version: MPAA rating: R; some strong sexuality, and language throughout.
DVD ; Dobly digital 5.1 surround (English, French, Spanish), DVS Dobly digital 2.0 stereo (English) ; widescreen (2.40:1).
English, French or Spanish dialogue with optional French or Spanish subtitles; English SDH.
Keywords: Bridesmaids -- Drama; Weddings -- Planning -- Drama